EFFECT OF ISO 9001: 2008 ON THE MOTIVATION AND PERFORMANCE OF STUDY EMPLOYEES AT THE STATE CIVIL SERVICES OFFICE CLASS 1 IMMIGRATION SURABAYA - Iqbal Ramadhani Fuadiputra (Universitas Bina Taruna Gorontalo, 2022)
This research is interesting to discuss the effect of ISO 9001:2008 on employee performance and employee motivation in the State Civil Apparatus (ASN) office. Surabaya City 1st class immigration service. In this study, the method used is a quantitative approach with the type of explanatory research. The sampling technique was based on purposive sampling with a total of approximately 70 civil servants. The data collection technique used a questionnaire and documentation, while the data analysis technique used in this study was a statistical test using SmartPLS. The results of this study indicate that the ISO 9001:2008 quality management standard influences employee motivation and performance in the level 1 immigration office in Surabaya. The results also show that one of the variable dimensions is an infrastructure dominant in employee motivation and performance. Performance in public services is one of the outputs produced and shows the quality of an organization. Public services in a government office have always been in the spotlight by some people. This condition causes the need for quality improvement and quality in public service management standards. To improve the quality, you can use the ISO 9001:2008 quality management system. In addition to performance, the change in motivation that is built up from the organization is also one of the impacts of the role of the ISO 9001 quality management system.